A Case of Sarcoidosis with Splenomegaly and Extrapulmonary Presentation - F Ghaffari; M Saravi; Z Khan Pour; Z Fotoukian; M Pouya; S Keihanian (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2010)
Sarcoidosis is a multisystem chronic disorder of unknown etiology that affects all of the organs, but the most commonly involved organs are the lungs. Pulmonary involvement is reported in 90% of patients and splenomegaly is reported in 20% of cases. In this study, we report one patient with sarcoidosis and splenomegaly without pulmonary involvement. Patient was a 52 years old, married housewife who referred to the hematology clinic with complaints of anemia, weight loss and high sedimentation. Results revealed minor normochromic normocytic anemia and splenomegaly. Because of low reticulocyte count and high ESR, biopsy and bone marrow aspiration was done to exclude malignancies and results showed erythroid hyperplasia and minor eosinophilia. Diagnostic splenectomy was also done and pathology reports of liver& spleen biopsy showed granulomatous inflammation and the presence of noncaseating granulomas in the involved organs. Final diagnosis was “Granulomatous inflammation” and the presence of noncaseating granulomas due to sarcoidosis. Patient was treated with prednisone. After splenectomy and onset of treatment, clinical presentation improved and patient gained weight. After one year of treatment and follow up, patient had no apparent clinical problem and treatment was stopped. Conclusion: Sarcoidosis is a rare disorder in Iran and difficult to differentiate from other liver & spleen disorders. It is necessary that proper diagnostic tests should be done for all patients so as to diagnose and treat sarcoidosis patients on time and prevent complications.